SIRT3 deacetylase: the Jekyll and Hyde sirtuin - Silberman, Dafne Magali (2011)
Post‐translational modifications have crucial roles in regulating the functions of many eukaryotic proteins. Among them, lysine acetylation has been traditionally studied in the context of nuclear histone modifications, and was one of the first to be described as part of the ‘histone code’ hypothesis (Kim et al, 2006). More recently, work from several groups has demonstrated that lysine acetylation also modulates the activity of several non‐histone proteins. In this context, this modification seems particularly abundant on mitochondrial proteins (Schwer et al, 2009). However, the way in which acetylation influences enzyme function and metabolic reprogramming in pathological states remains unknown. In an article published online this month in EMBO reports, Sack and colleagues shed new light on the role of mitochondrial SIRT3 deacetylase during paracetamol‐induced toxicity, describing the mitochondrial protein aldehyde dehydrogenase 2 (ALDH2) as a new target of SIRT3, and a protective role for protein acetylation in this context.